Planning for Madrasah Diniyah Awaliah Al-Ikhlas Mosque RW-06 Maharatu Village, Marpoyan Damai District - Pekanbaru City: Perencanaan Madrasah Diniyah Awaliah Masjid Al-Ikhlas RW-06 Kelurahan Maharatu Kecamatan Marpoyan Damai - Kota Pekanbaru - Fadrizal Lubis; Winayati Winayati; Virgo Trisep Haris Virgo (Institut Riset dan Publikasi Indonesia, 2022)
Planning a development requires more detailed details, so that in the field implementation there is no change. The Management of Al-Ikhlas Mosque RW-06 wants to establish the construction of the Early Early Madrasah (MDA). This is done because it is in accordance with Law No. 20 of 2003 concerning the National Education System and followed up or the adoption of PP No. 55 of 2007 as the basis for the need for religious education in Indonesia. Prior to the construction of Madrasah Diniyah Awaliah (MDA), detailed planning is needed in the form of designs (pictures). The results of the planning carried out are Siteplan Images, 1st and 2nd floor plans Front view, Side, Rear Pieces A-A and B-B, Cost Budget Plan (RAB) with a physical value of the building Rp.2,754,207,000, - including the value of VAT, Scheduling (Curve S) implementation time is ± 4 months in the work and adjusted to general and technical specifications. For the planning data manager, it is used as a basis or guide for doing further work.